OA01 Safety of vaccination against SARS-CoV-2 in people with rheumatic and musculoskeletal diseases: results from the EULAR Coronavirus Vaccine (COVAX) physician-reported registry. (23rd April 2022) - Machado, Pedro M; Lawson-Tovey, Saskia; Strangfeld, Anja; Mateus, Elsa; Hyrich, Kimme; Gossec, Laure; Carmona, Loreto; Rodrigues, Ana; Raffeiner, Bernd; Duarte, Cátia; Hachulla, Eric; Veillard, Eric; et al.
Abstract: Background/Aims: People with inflammatory/autoimmune rheumatic and musculoskeletal diseases (I-RMDs) were excluded from Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) vaccine clinical development programmes; therefore, concerns regarding the safety and effectiveness of SARS-CoV-2 vaccines in this population still exist. Previous studies in people with I-RMDs were small albeit reassuring in terms of the incidence of I-RMD flares and adverse events. Our aim was to describe the safety of vaccines against SARS-CoV-2 in people with I-RMD. Methods: Physician-reported registry of I-RMD and non-inflammatory RMD (NI-RMDs) patients vaccinated against SARS-CoV-2. From 5/Feb/2021 to 27/Jul/2021, we collected data on demographics, vaccination, RMD diagnosis, disease activity, immunomodulatory/immunosuppressive treatments, flares, adverse events (AEs) and SARS-CoV-2 breakthrough infections. Data were analysed descriptively. Results: The study included 5121 participants from 30 countries, 90% with I-RMDs (n = 4604, 68% female, mean age 60.5 years) and 10% with NI-RMDs (n = 517, 77% female, mean age 71.4). Inflammatory joint diseases (58%), connective tissue diseases (18%) and vasculitis (12%) were the most frequent diagnostic groups; 54% received conventional synthetic disease-modifying anti-rheumatic drugs (DMARDs), 42% biologic DMARDs and 35% immunosuppressants. Most patients received the Pfizer/BioNTech vaccine (70%), 17% AstraZeneca/Oxford and 8% Moderna. In fully vaccinated cases, breakthrough infections were reported in 0.7% of I-RMD patients and 1.1% of NI-RMD patients. I-RMD flares were reported in 4.4% of cases (0.6% severe), 1.5% resulting in medication changes. AEs were reported in 37% of cases (37% I-RMD, 40% NI-RMD), serious AEs in 0.5% (0.4% I-RMD, 1.9% NI-RMD). Conclusion: The safety profiles of SARS-CoV-2 vaccines in patients with I-RMD were reassuring, and comparable to patients with NI-RMDs. The majority of patients tolerated their vaccination well with rare reports of I-RMD flare and very rare reports of serious AEs. These findings should provide reassurance to rheumatologists and vaccine recipients, and promote confidence in SARS-CoV-2 vaccine safety in I-RMD patients. Disclosure: P.M. Machado: None. S. Lawson-Tovey: None. A. Strangfeld: None. E. Mateus: None. K. Hyrich: None. L. Gossec: None. L. Carmona: None. A. Rodrigues: None. B. Raffeiner: None. C. Duarte: None. E. Hachulla: None. E. Veillard: None. E. Strakova: None. G.R. Burmester: None. G.K. Yardimci: None. J.A. Gómez-Puerta: None. J. Zepa: None. L. Kearsley-Fleet: None. L. Trefond: None. M.M. Cunha: None. M. Mosca: None. M. Cornalba: None. M. Soubrier: None. N. Roux: None. O. Brocq: None. P. Durez: None. R. Conway: None. T. Goulenok: None. J.W.J. Bijlsma: None. I. McInnes: None. X. Mariette: None.